Evaluation of molecular typing methods to discriminate between isolates of Neisseria gonorrhoeae: Restriction endonuclease analysis, ribotyping and pulsed field gel electrophoresis. - Li, Hui. (University of Ottawa (Canada), 1994)
In the present study, three molecular methods, restriction enzyme (RE) analysis of chromosomal DNA, restriction fragment length polymorphism (RFLP) analysis of ribosomal RNA (rRNA) genes (ribotyping) and pulsed field gel electrophoresis (PFGE) were evaluated for their ability to discriminate within and between five groups of gonococcal isolates. By comparing the Re analysis and ribotyping for 100 gonococcal isolates as well as PFGE analysis for 26 of the 100 gonococcal isolates, there were twenty RE patterns, eleven ribotypes and twenty-five PFGE patterns produced. Overall, PFGE produced greater discrimination between isolates within the same A/S classes than ribotyping or RE analysis. In some cases, as with arginine-requiring strains or strains from an outbreak, several molecular methods should be tested in order to produce maximum discrimination between strains. Arginine auxotyphy is commonly encountered in Neisseria gonorrhoeae, comprising 40-60% of clinical isolates, including isolates with multiple nutritional requirement. Arginine (Arg) and uracil (U)-requiring strains are common in Canada. These AU isolates may have a deficiency affecting both the arginine and uracil biosynthesis pathways. Isolates may have a deficiency affecting both the arginine and uracil biosynthesis pathways. Isolates which require citrulline (C) alone for growth are very rare. Only 2 of 1540 of the arginine-requiring isolates in the culture collection of the NLSTD were citrulline-requiring. Strains requiring citrulline may be mutant for one of two enzymes, ornithine transcarbamoylase (OTCase), which catalyze L-citrulline formation from L-ornithine and carbamoylohosphate, or carbamoylphosphate synthetase (CPSase), which implicated in arginine and uracil biosynthesis pathways. Strains which are CPSase deficient may also be mutant in pyrimidine (U) biosynthesis. Twenty-two CU requiring isolates and two C requiring isolates were tested for OTCase and CPSase activities. The 22 CU auxotype possessed OTCase activity, but did not have CPSase activity. The 2 isolates requiring citrulline alone had CPSase activity, but did not have OTCase activity. (Abstract shortened by UMI.)
Keywords: Biology, Molecular.